2021
DOI: 10.2147/ijn.s309567
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyapatite/NELL-1 Nanoparticles Electrospun Fibers for Osteoinduction in Bone Tissue Engineering Application

Abstract: Background As commonly bone defect is a disease of jaw that can seriously affect implant restoration, the bioactive scaffold can be used as potential systems to provide effective repair for bone defect. Purpose A osteoinductive bone tissue engineering scaffold has been prepared in order to explore the effect of bioactive materials on bone tissue engineering. Methods In this study, NELL-1 nanoparticles (Chi/NNP) and nano hydroxyapatite were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…7 . It is observed that PCL-0 has a hydrophobic surface with a WCA of 127.1° ± 1.3°, which is consistent with previous reports 40 , 41 . With the addition of Ti 3 C 2 T X nanoflakes, the WCA of PCL-1 shows a slight decrease (115.3° ± 5.2°) due to the abundance of −OH groups on the surface of Ti 3 C 2 T X .…”
Section: Resultssupporting
confidence: 92%
“…7 . It is observed that PCL-0 has a hydrophobic surface with a WCA of 127.1° ± 1.3°, which is consistent with previous reports 40 , 41 . With the addition of Ti 3 C 2 T X nanoflakes, the WCA of PCL-1 shows a slight decrease (115.3° ± 5.2°) due to the abundance of −OH groups on the surface of Ti 3 C 2 T X .…”
Section: Resultssupporting
confidence: 92%
“…The highest osteogenic activity of MC3T3-E1 cells was observed on the 21st day of cell culture. The scaffold promoted cells' adhesion, proliferation, osteogenic differentiation, and maturation [85]. Three-component simultaneously electrospun layers scaffold incorporated PLGA and PEG or both with recombinant human vein endothelial growth factor (rhVEGF), recombinant human BMP-2 (rhBMP-2) factor, and Ca nanoparticles.…”
Section: Bioactive Scaffolds Incorporating Growth Factors Genes and E...mentioning
confidence: 99%
“…Previous studies have demonstrated that gadolinium silicate nanoparticles exhibit potential as MRI imaging agents and drug carriers through the encapsulation of anti-cancer drugs [21]. In another investigation, chitosan-coated bovine serum albumin (BSA) nanoparticles were developed to contain NELL-1, thereby stabilizing BSA microspheres and resulting in the controlled release of NELL-1, thereby enhancing its bioactivity [22]. Da et al have reported the fabrication of polyethylene glycolcoated Fe3O4-based nanoparticles loaded with doxorubicin as a drug carrier for tumor therapy.…”
Section: Introductionmentioning
confidence: 99%